Bodźcowość warunków termiczno-wilgotnościowych obszaru leśnego i terenu otwartego* - Dragańska, Ewa; Panfil, Monika; Szwejkowski, Zbigniew (Leśne Prace Badawcze, 2016)
Between 01.01.2010 and 31.12.2011, we conducted measurements of air temperature and relative humidity at points located deep within forest area, along the edge of the forest in the immediate vicinity of a lake and in open terrain. The thermal and humidity conditions that have a stimulating effect on human well-beeing were determined for the selected locations by calculating the number of hot (tmax≥ 25°C) and very hot days (tmax ≥ 30°C) as well as the number of frosty (tmax < 0°C) and very frosty days (tmin ≤ -10°C). The range of the stimulatory effect on human well-being by temperature was determined based on changes in the average night temperature and the amplitude of the daily air temperature. Stimulating humidity conditions were determined by comparing the relative humidity to a reference value associated with a moist feeling and calculating the number of humid days (s ≥18,8 mbar).